Application of spatial environmental indicators in the assessment of degradation potential of water resources in water basins - Arantes, Leticia Tondato [UNESP] (2023)
Changes in land use have been occurring in a continuous and disorderly way in recent decades due to rapid population growth and the growing demand for food. These constant changes result in a series of harmful effects to the environment, especially to water resources, significantly changing their availability and quality. This study aims to evaluate the degradation potential of watersheds through an evaluation of some environmental indicators using arithmetic means to construct an index called in this research “index of potential environmental degradation” (IPED). To form the IPED, the hydrographic sub-basins of the Sorocabuçu River, located in the central west of the State of São Paulo, Brazil, comprised the study area. The results showed that most hydrographic sub-basins, that is, eight units, present degradation values ranging from moderate to very high, resulting mainly from low conservation values of forests plus a use destined to the planting of temporary cultures depending on good physical conditions. On the other hand, only one sub-basin showed a low degradation value. The methodology used for the development of the IPED is easy to apply and an effective tool for environmental analyses. It may contribute to studies and forms of planning and land use management aiming the conservation of water resources and protected areas and reduction of degradation.